Effect of silica nanoparticles on physical, mechanical, and wear properties of natural fiber reinforced polymer composites. Issue 5 (2nd March 2021) - Singh, Tej; Gangil, Brijesh; Ranakoti, Lalit; Joshi, Amit
Abstract: Hemp‐sisal natural fiber‐reinforced hybrid epoxy composites containing a varying proportion of silica nanoparticles (0, 1, 2, 3, and 4 wt%) were manufactured and subsequently evaluated for physical, mechanical, and sliding wear properties. The density of the composite was found to increase, whereas void content was found to decrease with the increase of silica nanoparticles content. The composites containing 2 wt% silica nanoparticles exhibit maximum tensile strength, impact strength, and hardness, whereas the composite with 3 wt% silica nanoparticles showed the highest flexural strength. Dry sliding wear tests of the manufactured composites were carried out on a pin‐on‐disc machine under different sliding speeds, distances and applied loads at room temperature. Taguchi based L16 orthogonal array design was used to find the optimum combination of control factors resulting in higher wear resistance. The analysis reveals that the silica nanoparticles contribute the most towards wear performance with a contribution ratio of 32.61% and a combination of 2 wt% of silica nanoparticles, 10 N normal load, 1.5 m/s sliding speed and 500 m sliding distance resulted in higher wear resistance. Abstract :